Current Antibiotic-resistant crisis and initiatives to combat antimicrobial resistance: A review from global perspective - Bhowmick, Anaxme; Oishi, Tashrifa Shahreen; Aishy, Rideeta Islam (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2022.